Nanoporous silicon GRIN lenses. (31st January 2008) - Ilyas, Suhrawardi; Gal, Michael
We describe a novel application of nanoporous silicon as thin GRIN lenses. Positive and negative lenses can be made by achieving a continuous radial variation of the porosity during the fabrication of the layer. The gradient of refractive index in radial direction depends on resistivity of the silicon wafer and etching current density. The shape of the anode determines the type of lens. An electrode in the shape of a ring produces the positive lenses, while a point electrode produces the negative lens.